Pharmacologically Treated Anxiety and Depression in People Diagnosed with von Willebrand Disease: Matched Cohort Study - Hagberg KW; Jick S; Özen G; Du P (Journal of Blood Medicine, 2023)
Katrina Wilcox Hagberg,1 Susan Jick,1,2 Gülden Özen,3 Ping Du3 1Boston Collaborative Drug Surveillance Program, Lexington, MA, 02421, USA; 2Boston University School of Public Health, Boston, MA, 02118, USA; 3Takeda Development Center Americas, Inc., Cambridge, MA, 02139, USACorrespondence: Susan Jick, Boston Collaborative Drug Surveillance Program, 11 Muzzey Street, Lexington, MA, 02421, USA, Tel +1 781 862 6660, Fax +1 781 862 1680, Email sjick@bu.eduBackground: People diagnosed with von Willebrand disease (VWD) have reduced quality of life versus the general population, and there is limited evidence of increased rates of anxiety and/or depression among people diagnosed with VWD.Aim: To understand the association between VWD and mental health outcomes.Design and Setting: A retrospective cohort study was conducted using the UK Clinical Practice Research Datalink (CPRD) GOLD database (1988– 2016).Methods: People diagnosed with VWD were matched 1:10 to randomly selected people in the database without VWD based on sex, birth year ± 2 years, CPRD record start year ± 2 years, and general practice attended. Individuals were followed from VWD diagnosis or match date to censoring (first event date, CPRD end date, or death). Treated anxiety and treated depression were identified by a diagnostic Read Code and a prescription for anxiety/depression medication recorded within 90 days of each other, after VWD diagnosis/match date.Results: Treated anxiety was recorded in 89 of 1119 (8.0%) people diagnosed with VWD and 624 of 10,423 (6.0%) without VWD (age- and sex-adjusted incidence rate ratio [IRR], 1.37; 95% confidence interval [CI], 1.10– 1.71). Treated depression was recorded in 119 of 1083 (11.0%) people diagnosed with VWD and 846 of 9845 (8.6%) without VWD (adjusted IRR, 1.35; 95% CI, 1.11– 1.63). Females aged 20– 39 and 0– 19 years were at greatest risk for treated anxiety and treated depression, respectively.Conclusion: Higher rates of treated anxiety and depression were observed among people diagnosed with versus without VWD, predominantly in young females.Keywords: anxiety, depression, general practice, mental health, von Willebrand disease